Transforming Suzuki-Miyaura Cross-Couplings of MIDA Boronates into a Green Technology: No Organic Solvents - Isley, Nicholas A. (2013)
New technology has been developed that enables Suzuki-Miyaura couplings involving widely utilized MIDA boronates to be run in water as the only medium, mainly at room temperature. The protocol is such that no organic solvent is involved at any stage; from the reaction through to product isolation. Hence, using the E Factor scale as a measure of greenness, the values for all of these cross-couplings approach zero.